Children's feelings and attitude towards medical contacts - Bartosz Wojtera; Agnieszka Bugaj; Joanna Jackowska (Kazimierz Wielki University, 2021)
Introduction and purpose Medical procedures can be physically harmful and cause psychological trauma among young children, possibly resulting in certain lifelong aversion. The aim of the study was to evaluate children's feelings while undergoing minor medical procedures depending on age, gender and previous experience and to compare it with university students. Material and methods We conducted a survey among 382 primary school children, as well as 334 university students. Questions concerned the frame of mind at the moment of examination, during dentist and general physician appointment, vaccination, hospitalization and condition of sore throat. Results The experience of hospital stay resulted in better feelings about possible future hospitalization in both groups, and about dentist appointment in the group of children. Girls and women declared lower mood during general physician appointment. Interestingly, in the group of children boys felt worse at the moment of survey, while in the group of students women felt so. The current frame of mind correlated with an appraisal of all other situations among students, whereas only with physician appointment and vaccination among children. All of above were statistically significant. For both groups, the most unpleasant condition was sore throat. However, in regards to medical procedures exclusively, vaccination appeared to be the most traumatic for children and hospitalization for students. Conclusion Earlier experience and gender of children can affect their feelings about medical procedures. Presented analysis suggests that every medical should do their best to provide pleasant atmosphere for every child during medical contacts.